2022
DOI: 10.3390/children9081206
|View full text |Cite
|
Sign up to set email alerts
|

Sexual-Related Knowledge, School and Family Sexuality Education and Its Association with Experience of Sexual Intercourse among Vocational Secondary School Students in China

Abstract: Objectives: To investigate the associations between sexual-related knowledge, access to school and family sexuality education, and the experience of sexual intercourse, in order to make recommendations on sexuality education for vocational secondary school students in China. Methods: A cross-sectional study was conducted among 3180 vocational secondary school students in the Shanghai municipality and the Shaanxi province, China. Data were collected through an online, electronic questionnaire, which included so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
3
3
0
2
Order By: Relevance
“…We found that female students have better knowledge about sexuality than male students, which confirms our first hypothesis and is consistent with the results of other studies (Fang et al, 2022). However, other studies show no gender differences in (Phongluxa et al, 2020), which could be culturally conditioned.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that female students have better knowledge about sexuality than male students, which confirms our first hypothesis and is consistent with the results of other studies (Fang et al, 2022). However, other studies show no gender differences in (Phongluxa et al, 2020), which could be culturally conditioned.…”
Section: Discussionsupporting
confidence: 92%
“…We found that friends are an important source of information about sexuality, which is consistent with the results of a survey conducted in China (Fang et al, 2022). Several other studies have found that secondary school teachers can present an important source of information for adolescents regarding sexuality (Fang et al, 2022;Liškova et al, 2019;Ramirez -Villalobos et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those living in rural areas typically have a lower quality of education and receive fewer reproductive health services [25,30,31]. Compared with their rural counterparts who have limited education, women with higher education have stayed in school for a longer period and have fewer opportunities to make contact with society and engage in sexual intercourse [23,32]. The cumulative number of induced abortions in a cohort also increased with later cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this article, educational stratification will be used to refer to such class stratification that happened in Chinese high schools. However, previous youth studies in China rarely pay attention to vocational high school students, though few studies have tried to investigate the intersection of sexuality education and educational stratification (Fang et al, 2022; Liu, 2022). Therefore, through interviews with high school students and schoolteachers in an academic high school and a vocational high school in Tianjin, China, this article will contribute to filling such gap by providing information on how Chinese young people deal with their excitement, curiosity and concerns about sexuality and heterosexual romantic relationships in their high-school ages.…”
Section: Introductionmentioning
confidence: 99%